2018
DOI: 10.1093/gigascience/giy058
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of evolutionary history and selective sweeps in the genome of Meishan pig reveals its genetic and phenotypic characterization

Abstract: BackgroundMeishan is a pig breed indigenous to China and famous for its high fecundity. The traits of Meishan are strongly associated with its distinct evolutionary history and domestication. However, the genomic evidence linking the domestication of Meishan pigs with its unique features is still poorly understood. The goal of this study is to investigate the genomic signatures and evolutionary evidence related to the phenotypic traits of Meishan via large-scale sequencing.ResultsWe found that the unique domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 60 publications
(62 reference statements)
4
46
0
Order By: Relevance
“…Chickens from neighboring geographical locations and from similar altitudes are gathered together. Gene exchanges are likely to be correlated with geographical location, which is consistent with results from previous studies [14,24,[31][32][33]. Population genomics analysis, including PCA, NJ tree, and structure, reveal that red jungle fowl can be separated into two branches, possibly because there have been different venues for domestication [17,34,35].…”
Section: Discussionsupporting
confidence: 87%
“…Chickens from neighboring geographical locations and from similar altitudes are gathered together. Gene exchanges are likely to be correlated with geographical location, which is consistent with results from previous studies [14,24,[31][32][33]. Population genomics analysis, including PCA, NJ tree, and structure, reveal that red jungle fowl can be separated into two branches, possibly because there have been different venues for domestication [17,34,35].…”
Section: Discussionsupporting
confidence: 87%
“…We found that a gene could elucidate the genetic basis of coat color phenotype of ASP population. In previous studies about pig coat color, MC1R gene was under positive selection (Li et al, 2010;Zhao et al, 2018). In this study, the MC1R gene was also found under selection based on cross approaches.…”
Section: Discussionmentioning
confidence: 62%
“…The strictly organized breeding program was adopted to improve and develop livestock breeds, Britain, in particular, was the main center of the early improvement of pig breeds and cultivated the famous Yorkshire pigs [34]. FRA-Y was regarded as the pigs most likely to contain ancestries of Chinese local pigs [35]. Canada and the United States are far from the origin country of the Yorkshire-Britain and FRA-Y, CAN-Y and USA-Y were thus used in the study.…”
Section: Discussionmentioning
confidence: 99%